The clinical perspective in fieldwork - Schein, Edgar H. (Newbury Park, Calif. ; London : SAGE, 1987)
Edgar Schein succinctly outlines the clinical perspective in field research, how it differs from other types of qualitative research and its inherent rewards and difficulties.
"A SAGE university paper."
Includes bibliographical references.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Social sciences -- Research -- Methodology; Social sciences -- Fieldwork; Clinical sociology; Qualitative research